2008
DOI: 10.1007/s11581-008-0267-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical characteristics of sulfur composite cathode for reversible lithium storage

Abstract: The electrochemical characteristics of the sulfur composite cathode for reversible lithium storage were investigated. The sulfur composites showed novel electrochemical characteristics as well as high specific capacity and good cycleability. The sulfur composite presented the average discharge voltage of 1.9 V, which was just the half of conventional LiCoO 2 cathode materials, indicating that the double cells in series presented the same working voltage as conventional LiCoO 2 cells and meaning that the sulfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…[ 30 ] In spite of their instability with the presence of polysulfi de anions, carbonate-based electrolytes have proven to be safe with cathode composites in which sulfur was either physically confi ned within micro-sized pores of a carbon structure, which avoided polysulfi de dissolution to the electrolyte, or covalently immobilized in polymeric composites. [ 38,46,165,170,177,[179][180][181] For example, Wang et al demonstrated this effect with sulfur in a microporous-mesoporous carbon material, [ 46 ] and Xin et al did the same with metastable small sulfur molecules of S 2-4 in a microporous carbon matrix. [ 38 ] At present, the preferred ether solvents in Li-S cells are dimethyl ether (DME), [ 24,72,161 ] tetra(ethylene glycol) dimethyl ether (TEGDME), [ 70,72,80,123,169 ] polyethylene glycol dimethyl ether (PEGDME), and 1,3-dioxolane (DOL), [ 69,85,161,171,[182][183][184] with lithium bis(trifl uoromethanesulfonyl)imide (LiTFSI) as the Li + ion carrier.…”
Section: Solvents' Impact On the Dissolved Polysulfi De Speciesmentioning
confidence: 99%
“…[ 30 ] In spite of their instability with the presence of polysulfi de anions, carbonate-based electrolytes have proven to be safe with cathode composites in which sulfur was either physically confi ned within micro-sized pores of a carbon structure, which avoided polysulfi de dissolution to the electrolyte, or covalently immobilized in polymeric composites. [ 38,46,165,170,177,[179][180][181] For example, Wang et al demonstrated this effect with sulfur in a microporous-mesoporous carbon material, [ 46 ] and Xin et al did the same with metastable small sulfur molecules of S 2-4 in a microporous carbon matrix. [ 38 ] At present, the preferred ether solvents in Li-S cells are dimethyl ether (DME), [ 24,72,161 ] tetra(ethylene glycol) dimethyl ether (TEGDME), [ 70,72,80,123,169 ] polyethylene glycol dimethyl ether (PEGDME), and 1,3-dioxolane (DOL), [ 69,85,161,171,[182][183][184] with lithium bis(trifl uoromethanesulfonyl)imide (LiTFSI) as the Li + ion carrier.…”
Section: Solvents' Impact On the Dissolved Polysulfi De Speciesmentioning
confidence: 99%
“…[ 75,83 ] In fact, it was recently demonstrated that an all carbon-based Li-ion system can be assembled from S-PAN cathodes and graphite, an anode that requires the carbonate-based electrolyte for optimal function. [ 104 ] However, there are no convenient and scalable methods for pre-lithiating these electrode materials. This remains a challenge that must be addressed in order to replace lower capacity Li-ion battery cathodes.…”
Section: Covalent Attachmentmentioning
confidence: 99%
“…The reported advantages of the SPAN over elemental sulfur include: (1) it offers very stable specific capacity close to or even higher than the theoretical value of elemental sulfur; (2) it completely avoids the dissolution of long-chain lithium polysulfide (PS) in organic electrolyte, as well as the resulting redox shuttle and parasitic reactions with lithium anode; (3) it is chemically compatible with the LiPF 6 -carbonate based electrolytes widely used in the state-of-art Li-ion batteries; (4) it suits for the cathode with high active material loading; and (5) the Li/SPAN cell after activation has nearly 100% coulombic efficiency (CE) and extremely low self-discharge rate. Moreover, He et al have successfully demonstrated a proof-of-concept "all carbon" Li-ion battery by electrochemically pre-lithiating a graphite anode and then coupling the pre-lithiated graphite anode with a SPAN cathode [6]. The dream to fabricate safe and low cost metal-free Li-ion batteries will become true once a viable process for the pre-lithiation of either SPAN cathode or carbonaceous (or others such as silicon, tin, and their relative alloys) anode can be successfully developed.…”
Section: Introductionmentioning
confidence: 99%